Ileal excretion and bacterial modification of bile acids and cholesterol in patients with continent ileostomy. Issue 2 (February 1980) - Kay, R M; Cohen, Z; Siu, K P; Petrunka, C N; Strasberg, S M
Abstract : Bile acid (acidic sterol) and neutral steroid excretion were determined in 15 patients, five with conventional ileostomy, five with continent ileostomy, and five with continent ileostomy and an ileal resection. Acidic sterol losses were normal in conventional ileostomy patients and not significantly increased in those with continent ileostomy alone. Bile acid excretion rates were significantly increased in patients with a continent ileostomy and an ileal resection. Neutral steroid excretion was similar in all groups and not different from normal. Deoxycholic acid was not detected in ileal effluent of patients with conventional ileostomy and less than 2% of neutral steroid excreted was in the form of bacterial metabolites of cholesterol. The same was true of six of the 10 patients with continent ileostomies; in the other four patients at least 10% of acidic or neutral steroids were excreted as secondary bile acids or as a coprostanol. Modification of steroids was not related to ileal resection. Continent ileostomy was associated with a significant increase in percentage water content and a reduction in the pH of ileal effluent.